Optical Connecting of Fibers by Laser Beams Propagating from the Fibers Edges. (9th April 2008) - Mensov, Sergey Nikolayevich; Polushtaytsev, Yuri Victorovich
Abstract : A possibility to connect nonprecise positioned fibers in photopolymerizable compositions is under discussion in this paper. The processes of optical synthesis of connective waveguiding structures forming in such mediums directly by the radiation leaving the edges of connecting fibers are investigated numerically and experimentally as well. It was shown that nonlinear interaction of the light beams allows to connect misaligned and transversally shifted fibers with high efficiency.